Exploring gait adaptations to perturbed and conventional treadmill training in Parkinson’s disease: time-course, sustainability, and transfer - Steib, Simon; Klamroth, Sarah; Gaßner, Heiko; Pasluosta, Cristian; Eskofier, Björn; Winkler, Jürgen; Klucken, Jochen; Pfeifer, Klaus (Human movement science, 2019)
Background - Gait impairment is a major motor symptom in Parkinson’s disease (PD), and treadmill training is an effective non-pharmacological treatment option. - Research question - In this study, the time course, sustainability and transferability of gait adaptations to treadmill training with and without additional postural perturbations were investigated. - Methods - 38 PD patients (Hoehn & Yahr 1-3.5) were randomly allocated to eight weeks of treadmill training, performed twice-weekly for 40min either with (perturbation treadmill training [PTT], n=18) or without (conventional treadmill training [CTT], n=20) additional perturbations to the treadmill surface. Spatiotemporal gait parameters were assessed during treadmill walking on a weekly basis (T0-T8), and after three months follow-up (T9). Additional overground gait analyses were performed at T0 and T8 to investigate transfer effects. - Results - Treadmill gait variability reduced linearly over the course of 8weeks in both groups (p<.001; Cohen’s d (range): −0.53 to −0.84). Only the PTT group significantly improved in other gait parameters (stride length/time, stance-/swing time), with stride time showing a significant between-group interaction effect (Cohen’s d=0.33; p=.05). Additional between-group interactions indicated more sustained improvements in stance (Cohen’s d=0.85; p=.02) and swing time variability in the PTT group (Cohen’s d=0.82; p=.03) at T9. Overground gait improvements at T8 existed only in stance (d=-0.73; p=.04) and swing time (d=0.73; p=.04). - Discussion - Treadmill stride-to-stride variability reduced substantially and linearly, but transfer to overground walking was limited. Adding postural perturbations tended to increase efficacy and sustainability of several gait parameters. However, since between-group effects were small, more work is necessary to support these findings.